Is there a difference in body size dissatisfaction between the patients with obesity seeking and not seeking treatment for obesity? - Wojciech Gruszka; Aleksander J. Owczarek; Mateusz Glinianowicz; Monika Bąk-Sosnowska; Jerzy Chudek; Magdalena Olszanecka-Glinianowicz (BMC, 2021)
Abstract Background Various factors motivate people to undertake treatment for obesity. Among others they include health benefits, willingness to please others, and dissatisfaction with one's appearance. The present study aimed to assess body size dissatisfaction in patients with obesity seeking and not seeking treatment for obesity. Methods Two-hundred-sixteen adult subjects (154 women, 62 men) including 80 people with BMI ≥ 30 kg/m2 starting treatment for obesity (BMI 35.7 ± 5.3 kg/m2) and 136 volunteers with obesity (BMI 34.7 ± 4.3 kg/m2) not seeking treatment for obesity, were enrolled. Body size satisfaction was assessed using the Figure Rating Scale adapted by Stunkard. Results Patients with obesity starting obesity treatment had more often a high level of body size dissatisfaction than volunteers with obesity not seeking the treatment (p <  0.001). There was a significant difference in the distribution of body size dissatisfaction in women (p <  0.05), but not in men (p = 0.47). Conclusion Patients with obesity, especially women, seeking obesity treatment more often represent a high level of body size dissatisfaction than volunteers with obesity not seeking treatment for obesity. This implies the need for public health campaigns to address negative attitudes or misconceptions about obesity and its treatment. Placing more attention and emphasis on body size dissatisfaction in more vulnerable women with obesity may help to define personal motivations and goals, strengthen the doctor-patient relationship and better adapt therapeutic strategies.